Anthony Giddens : the last modernist - Meštrović, Stjepan Gabriel (London ; New York : Routledge, 1998)
Anthony Giddens is arguably the world's leading sociologist. In this controversial contribution to the Giddens debate, Stjepan Mestrovic takes up and criticizes the major themes of his work - particularly the concept of 'high modernity' as opposed to 'postmodernity' and his attempted construction of a 'synthetic' tradition based on human agency and structure. Testing Giddens' theories against what is happening in the real world from genocide in Africa to near secession in Quebec, Mestrovic discerns in the construction of synthetic traditions not the promise of freedom held out by Giddens but r.
BOOK COVER; HALF-TITLE; TITLE; COPYRIGHT; DEDICATION; CONTENTS; PREFACE AND ACKNOWLEDGMENTS; 1 INTRODUCTION; 2 ANTHONY GIDDENS; 3 THE NEW VERSUS THE OLD RULES OF SOCIOLOGICAL METHOD; 4 THE ROLE OF DESIRE IN AGENCY AND STRUCTURE; 5 GIDDENS'S POLITICAL SOCIOLOGY; 6 GIDDENS'S MODERNISM LITE; 7 UNLIMITED AGENCY AS THE NEW ANOMIE; 8 CONCLUSIONS; NOTES; REFERENCES; INDEX.
Includes bibliographical references (pages 222-231) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Giddens, Anthony; Giddens, Anthony; Giddens, Anthony; Sociology -- Methodology; Postmodernism; Social structure; Sociology -- Great Britain; Sociologie -- Méthodologie.; Postmodernisme; Structure sociale; Sociologie -- Grande-Bretagne.; social structure; SOCIAL SCIENCE -- Regional Studies; SOCIAL SCIENCE -- Anthropology -- General; Postmodernism; Social structure; Sociology; Sociology -- Methodology; Great Britain; Sociologie; Moderniteit